Bacterial Community Structure and Functional arrA Gene Diversity Associated with Arsenic Reduction and Release in an Industrially Contaminated Soil. Issue 10 (25th November 2016) - Quéméneur, Marianne; Garrido, Francis; Billard, Patrick; Breeze, Dominique; Leyval, Corinne; Jauzein, Michel; Joulian, Catherine
ABSTRACT: This study aimed at evaluating potential arsenic (As) mobility in an industrially contaminated soil (64 mg/kg of As) of the Meuse River basin, and at identifying key bacterial groups that drive soil As dynamics. Both speciation and release of As from this soil was followed under anaerobic conditions using a laboratory batch experiment. In the presence of exogenous carbon sources, As V initially present in the soil matrix and/or adsorbed on synthetic hydrous ferric oxides were solubilized and mainly reduced to As III by indigenous soil microflora. After a 1-month incubation period in these biotic conditions, As III accounted for 80–85% of the total dissolved As and more than 60% of the solid-phase As. Bacterial community structure (i.e., 16S rDNA-based capillary electrophoresis single-strand conformation polymorphism profiles) changed with incubation time and As amendment. The detection of distantly related arsenate respiratory reductase genes ( arrA ), as functional markers of As V respirers, indicates that novel dissimilatory As V -reducing bacteria may be involved in As biotransformation and mobility in anoxic soils. Since As and iron were concomitantly released, a crucial role of indirect As-mobilizing bacteria on As behavior was also revealed. Our results show that the majority of As within the soil matrix was bioavailable and bioaccessible for heterotrophic As V reduction to As III, which may increase As toxicity and mobility in the contaminated soils.